Association between the metabolic syndrome parameters and serum level of uric acid - Mojgan Motevally Bashi; Zahra Davoudi; Mohammad Salehi; Seyed Hadi Mirhashemi (Society of Diabetic Nephropathy Prevention, 2022)
Introduction: It is well-known that metabolic syndrome is a pathophysiological state with increased risks for diabetes mellitus (DM) and the atherosclerotic cardiovascular disease. Moreover, hyperuricemia can be considered as the main component in metabolic syndrome. Objectives: The present research aimed at the investigation of the association between serum level of uric acid with metabolic syndrome parameters. Patients and Methods: The present cross-sectional study population consisted of 200 subjects susceptible to metabolic syndrome. Data related to weight, height, waist circumference, body mass index (BMI), history of the disease, as well as drug consumption were recorded. All patients underwent routine blood tests for C-reactive protein (CRP ) as well as uric acid levels. According to the diagnostic criteria for metabolic syndrome, we divided the patients into two groups. The first group was affected by metabolic syndrome(case) and the second was without metabolic syndrome (control). Then, we utilized Pearson's correlation coefficient to investigate the correlation of the serum level of uric acid with the continuous metabolic syndrome parameters. Finally, significant level was P<0.05 throughout this survey. Results: In the case group, the level of uric acid was higher (6.55 ± 1.24 mg/dL) than the control level (4.76 ± 1.24 mg/dL) (P<0.001). We found a significant correlation between the uric acid level and hip circumference, waist circumference, fasting blood sugar, and CRP only in obese patients. Conclusion: As demonstrated, a positive association between the level of serum uric acid and BMI ≥30 kg/m2 in the case group suggests greater role of obesity in metabolic syndrome. Since there is a strong correlation between serum CRP and uric acid levels in the case group with BMI ≥30 kg/m2 . High plasma concentration of uric acid can be an inflammatory marker and risk factor for obesity. Therefore, obese people with metabolic syndrome are recommended to control their hyperuricemia.